Effects of stem cell therapy on dilated cardiomyopathy - Jiao, Rong; Liu, Yuan; Yang, Wen-Jian; Zhu, Xiao-Yan; Li, Jin; Tang, Qi-Zhu (Saudi Medical Journal, 2014)
OBJECTIVES: To perform a meta-analysis of clinical trials and investigate the effect of stem cell therapy on dilated cardiomyopathy.METHODS: A systematic literature search was carried out between May 2012 and July 2013 in PubMed, Medline, Cochrane Library, and Excerpta Medica Database (EMBASE). The study took place in the Department of Cardiology, Renmin Hospital of Wuhan University, Wuhan, China. The weighted mean difference (WMD) was calculated for left ventricular ejection fraction (LVEF), left ventricular end-diastolic diameter (LVEDD), mortality and heart transplantation, and the 6-minute walk test (6-MWT) distance using the RevMan 5.0 software.RESULTS: Seven trials with 599 participants evaluated the association between the stem cell therapy and control groups. Compared with the control group, stem cell therapy group improved the LVEF (WMD: 3.98%, 95% confidence interval [CI]: 0.55 - 7.41%, p=0.02) and the 6-MWT distance (WMD: 132.12 m, 95% CI: 88.15-176.09 m, p<0.00001), and reduced mortality and heart transplantation (odds ratio [OR]: 0.48, 95% CI: 0.29-0.80, p=0.005). However, the LVEDD showed no significant difference between the 2 groups (WMD: -1.53 mm, 95% CI: -1.15-0.10 mm, p=0.10).CONCLUSION: This meta-analysis demonstrated that stem cell therapy improves cardiac function and reduces mortality in dilated cardiomyopathy patients, which suggested that stem cell therapy may represent a new therapy option for dilated cardiomyopathy.